IMPROVING STUDENTS’ READING COMPREHENSION IN NARRATIVE TEXT BY USING QUESTIONS ANSWER RELATIONSHIP STRATEGY - Katia, Reyna; Apriliaswati, Rahayu; suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was conducted based on the problems in teaching learning process. The students had problems to comprehend the information in the generic structure of the narrative text, they were lack of vocabulary, and they did not know how to use reading strategies to comprehend narrative text. The purpose of this research was to investigate how Questions Answer Relationship (QAR) strategy enhanced students’ reading comprehension of narrative text at the Ninth Grade students of SMPN 2 Pontianak in academic year 2017/2018. The research was conducted through Classroom Action Research in three cycles. The participants of this research were the ninth grade English teacher and 38 students in class IX B. The writer used observation, and measurement technique to collect the data. The writer elaborated the result of observation checklist, field note, and students’ mean score, in order to get the research findings. The result showed that students could comprehend a narrative text through QAR strategy. QAR strategy improved students’ vocabulary, students’ understanding of information in the narrative text, and students’ understanding in applying reading strategies. In the first cycle, the students’ mean score was 58.8, it increased to 68.6 in the second cycle, and it increased to 80.3 in the third cycle. In other words, Question Answer Relation (QAR) strategy improved students’ reading comprehension of narrative text. Keywords: reading comprehension, narrative text, Question Answer Relationship strategy